Detrimental role of IL-33/ST2 pathway sustaining a chronic eosinophil-dependent Th2 inflammatory response, tissue damage and parasite burden during Toxocara canis infection in mice. - Thaís Leal-Silva (Public Library of Science (PLoS), 2021)
Toxocariasis is a neglected disease that affects people around the world. Humans become infected by accidental ingestion of eggs containing Toxocara canis infective larvae, which upon reaching the intestine, hatch, penetrate the mucosa and migrate to various tissues such as liver, lungs and brain. Studies have indicated that Th2 response is the main immune defense mechanism against toxocariasis, however, there are still few studies related to this response, mainly the IL-33/ST2 pathway. Some studies have reported an increase in IL-33 during helminth infections, including T. canis. By binding to its ST2 receptor, IL-33 stimulating the Th2 polarized immune cell and cytokine responses. Thus, we aimed to investigate the role of the IL-33/ST2 pathway in the context of T. canis larval migration and the immunological and pathophysiological aspects of the infection in the liver, lungs and brain from Wild-Type (WT) BALB/c background and genetically deficient mice for the ST2 receptor (ST2-/-). The most important findings revealed that the IL-33/ST2 pathway is involved in eosinophilia, hepatic and cerebral parasitic burden, and induces the formation of granulomas related to tissue damage and pulmonary dysfunction. However, ST2-/- mice, the immune response was skewed to Th1/Th17 type than Th2, that enhanced the control of parasite burden related to IgG2a levels, tissue macrophages infiltration and reduced lung dysfunction. Collectively, our results demonstrate that the Th2 immune response triggered by IL-33/ST2 pathway mediates susceptibility to T. canis, related to parasitic burden, eosinophilia and granuloma formation in which consequently contributes to tissue inflammation and injury.